Application of Good Governance Principles in Land Acquisition for Cemeteryn Masangan Kulon Village, Sukodono District, Sidoarjo Regency - Aziza, Meilina Nur; Arif, Lukman (ARISTO, 2022)
Land acquisition for the cemetery in Masangan Kulon Village was an initiative of the residents of the Griya Bhayangkara Residence Masangan Kulon because the cemetery land was full, and there had been no development for 17 years. Referring to Law number 2 of 2012 and PP RI number 9 of 1987, land acquisition for the cemetery is also an area designated for society provided by the government. This is not only society's responsibility but also the government's responsibility, so an approach based on the principles of good governance is needed. This study aims to analyze and describe the principles of good governance in land acquisition for cemeteries in Masangan Kulon Village. This descriptive qualitative research collects data through observation, interviews, and documentation. The research focus uses the nine principles of good governance according to UNDP: participation, rule of law, transparency, responsiveness, consensus orientation, equity, effectiveness and efficiency, accountability, and strategic vision. This research used purposive sampling technique and interactive model data analysis. The results of the study show that the application of the principles of good governance in the land acquisition for the cemetery in Masangan Kulon has run very well. Even though the rule of law principles have not been implemented optimally, the other eight principles have been appropriately implemented and optimally